Case series on herbal medication induced acute kidney injury in central India - Vinay Kumar A. V.; Rathore, Vinay; Vijayalakshmi Shanbhag (International Journal of Research in Medical Sciences, 2023)
Around 60 to 70 percent of the people from India reside in rural areas and usually opt for herbal medicine for illness from local traditional medicine practitioners before seeking allopathic advice. Kidneys play a central role in excretion of the metabolites of these substances or the substances themselves. Renal injury happens in the form of acute tubular necrosis, interstitial nephritis, rhabdomyolysis, nephrolithiasis, urothelial cancers and rarely renal cortical necrosis and progressive interstitial fibrosis. Physicians and patients may ignore the potential nephrotoxicity caused by certain herbal medicines, assuming them to be harmless. Adverse event reporting is usually done on a voluntary basis, and toxicity has been reported through case reports and series. It is important for clinicians to factor in the use of herbal medicines when treating patients with unexplained acute kidney injury or progressive chronic kidney disease. We hereby present a case series of renal injury mediated by herbal medications with different mechanism of injury to kidney. This article is first of its type reported from central India.